Productivity of zero-till wheat (Triticum aestivum) under different establishment methods, seed rate and weed control - BARUA, MOUMITA; KAUR, TARUNDEEP; BHULLAR, MAKHAN S; GILL, JASVIR SINGH (The Indian Journal of Agricultural Sciences, 2021)
Field experiment was planned to investigate the integration of establishment methods, variable seed rates and weed control in zero-till wheat (Triticum aestivum L.). The experiment was conducted in split-plot design with four replications. Treatments consisted of two establishment methods, i.e. zero till wheat with residue, viz. ZT+R (6 t/ha) and zero till wheat without residue, viz. ZT-R (0 t/ha), two levels of wheat seed rate (100 kg/ha (recommended) and 150 kg/ha) and four levels of weed control (weedy check, weed free, clodinafop + metribuzin 275 g/ha (recommended) and clodinafop + metribuzin 206.3 g/ha). The results revealed that clodinafop + metribuzin 275 g/ha in ZT + R had significantly lower P. minor biomass (25-27%) than ZT-R; however 16 and 14%biomass of broadleaved weeds were recordedat 90 days after sowing. Interaction effect revealed that in 2017-18, under weedy check, ZT+R had lower weed biomass and gave 14.9% higher grain yield than ZT-R; however in 2016-17, both ZT+R and ZT-R methods recorded almost similar yield. Integrated use of clodinafop+metribuzin 275 g/ha in zero till wheat sown in paddy residues gave the highest wheat grain yield (5465-5531 kg/ha) which was similar to weed free.